Tolong jawab
1.) (1/5)^-1 . (5/7)^-2 = ...
2.) (1/5)^-1 ÷ (5/7)^-2 = ...
1.) (1/5)^-1 . (5/7)^-2 = ...
2.) (1/5)^-1 ÷ (5/7)^-2 = ...
Penjelasan dengan langkah-langkah:
[tex] ({ \frac{1}{5}) }^{ - 1} \times ({ \frac{5}{7}) }^{ - 2} = \\ 5 \times { (\frac{7}{5} )}^{2} = \\ 5 \times \frac{49}{25} = \frac{49}{5} = 9 \frac{4}{5} [/tex]
[tex] {( \frac{1}{5}) }^{ - 1} \div { \frac{5}{7} }^{ - 2} = \\ 5 \div { \frac{7}{5} }^{2} = \\ 5 \times \frac{25}{49} = \\ \frac{125}{49} = 2 \frac{27}{49} [/tex]
[answer.2.content]